Marginal SARS-CoV-2 Spike Protein Increases Interferon and Balances Cytokine Gene Expression - Satadal Das; Debasmita Chatterjee; Krishnendu Paira (International Journal of Coronaviruses, 2022)
Some evidence confirms the paradoxical beneficial role of harmful antigens when used in highly diluted forms. In this experiment, we observed cytokine gene expression changes in Gallus gallus embryo after challenge with Delta SARS-CoV-2 RBD spike protein antigen, from a concentration of 10 µg/mL to a series of highly diluted forms in ethanol, along with controls. We have also studied pre-and post- experimental combined sets of higher (10 µg/mL) and significantly lower antigen concentrations (attogram level). Attogram and zeptogram level concentrations of the antigen showed consistently remarkable up-regulation of INF-α among different cytokine gene expressions. INF-β gene expressions at the zeptogram level of the antigen showed consistent changes, although not so outstanding. The pre-experimental set having attogram level antigen administered first, followed by a 10µg/mL antigen challenge, showed excellent cytokine balance. Other experimental groups, including the control sets, showed variable results at different concentrations.
Keywords: SARS-CoV-2